Taurine ameliorates volatile organic compounds-induced cognitive impairment in young rats via suppressing oxidative stress, regulating neurotransmitter and activating NMDA receptor - Gao, Yongchao; Sun, Chao; Gao, Ting; Liu, Zhiyong; Yang, Zhao; Deng, Hui; Fan, Peng; Gao, Junhong (Frontiers in Veterinary Science, 2022)
Long-term exposure to volatile organic compounds (VOCs) in children leads to intellectual and cognitive impairment. Taurine is an essential nutritional amino acid for children, which can improve neurological development in children. However, the neuroprotective effect of taurine on VOCs-induced cognitive impairment in children remains unclear. The aim of this study was to investigate the neuroprotective effects of taurine on VOCs-induced cognitive impairment in young rats. The rats were nose-only exposed to VOCs for a period of 4 weeks to create a model of cognitive impairment, and 0.5% and 1% taurine in tap water were administered throughout the trial period, respectively. Our results showed that young rats adjusted the recovery of their physiological functions by voluntarily increasing the intake of taurine in tap water when exposed to excessive VOCs by inhalation. In addition, taurine enhanced grasp, shortened the latency period of escape, and improved the learning and memory function of young rats. Moreover, taurine decreased malondialdehyde (MDA), γ-aminobutyric acid (GABA), Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Urea, Creatinine (CREA) and injury biomarker level, enhanced superoxide dismutase (SOD), reduced glutathione (GSH) and glutamic acid (Glu) activities, up-regulated the protein expression of brain derived neurotrophic factor (BDNF) and N-Methyl-d-aspartate receptor 1 (NMDAR1) in model rats, and in most of cases 1% but not 0.5%, ameliorated the defects induced by VOCs. Collectively, these findings suggested that taurine protected against VOCs-induced cognitive-behavioral impairment in young rats through inhibiting oxidative stress and regulating neurotransmitter homeostasis. In addition, taurine were capable of restoring abilities of learning and memory in young rats exposed to VOCs by activating the N-Methyl-d-aspartate (NMDA) receptor. The findings suggest taurine as a potential novel drug for the treatment of cognitive behavioral disorders in children.